2014
DOI: 10.1186/preaccept-2067133308130116
|View full text |Cite
|
Sign up to set email alerts
|

Seeking informal and formal help for mental health problems in the community: a secondary analysis from a psychiatric morbidity survey in South London

Abstract: Background: Only 30-35% of people with mental health problems seek help from professionals. Informal help, usually from friends, family and religious leaders, is often sought but is under-researched. This study aimed to contrast patterns of informal and formal help-seeking using data from a community psychiatric morbidity survey (n=1692) (South East London Community Health (SELCOH) Study). Methods: Patterns of help-seeking were analysed by clinical, sociodemographic and socioeconomic indicators. Factors associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 23 publications
8
40
5
Order By: Relevance
“…While psychiatrists and other clinicians showed stable rates over time, psychologist referral revealed a non‐significant increase (6% to 12% to 15%) whereas neurologist referral had a statistically significant reduction (23% to 7% in the following epochs). Even though overall numbers of psychiatrists and other physicians likely increased in Italy over time (in a way that the present study could not assess), taken as a whole, our data indicate that psychiatrists are responsible for first contact and treatment in patients with mental disorders in less than 50% of the cases (45% on average), while other clinicians (e.g., primary‐care physicians) are responsible in almost one‐third of cases (34% on average) . The increase in psychologist referral may be partly responsible for an overall reduced latency to treatment in cases of integrated treatment (psychotherapy followed by pharmacological treatment), likey reflecting an efficient synergy between psychologists and psychiatrists.…”
Section: Discussionmentioning
confidence: 57%
“…While psychiatrists and other clinicians showed stable rates over time, psychologist referral revealed a non‐significant increase (6% to 12% to 15%) whereas neurologist referral had a statistically significant reduction (23% to 7% in the following epochs). Even though overall numbers of psychiatrists and other physicians likely increased in Italy over time (in a way that the present study could not assess), taken as a whole, our data indicate that psychiatrists are responsible for first contact and treatment in patients with mental disorders in less than 50% of the cases (45% on average), while other clinicians (e.g., primary‐care physicians) are responsible in almost one‐third of cases (34% on average) . The increase in psychologist referral may be partly responsible for an overall reduced latency to treatment in cases of integrated treatment (psychotherapy followed by pharmacological treatment), likey reflecting an efficient synergy between psychologists and psychiatrists.…”
Section: Discussionmentioning
confidence: 57%
“…Research has shown for example, that many people in low-income communities face a range of culturally determined issues that deter them from seeking help, and that this is particularly evident amongst men (Clement et al, 2015). Other studies have stressed the value of informal social networks that enable people to share their experiences amongst trusted networks (Brown et al, 2014), and more work is needed to better understand how such mechanisms function and how they can be effectively fostered and supported.…”
Section: Responding To Distressmentioning
confidence: 99%
“…Furthermore, in a large national populationbased sample, subjects tended to endorse informal rather than formal help when they were asked how they would cope in the case of psychological problems [66]. The importance of informal help-seeking was also highlighted in another community study [67] and a clinical sample [68]. It is surprising then that informal help-seeking has generally been less investigated than formal help-seeking.…”
Section: Copingmentioning
confidence: 99%